The AGROVOC Concept Scheme – A Walkthrough - Sachit Rajbhandari; Johannes Keizer (Journal of Integrative Agriculture, 2012)
The Food and Agriculture Organization is developing a concept based multilingual vocabulary management tool to manage thesauri, authority lists and glossaries expressed as concept schemes ready to be used in a linked data environment. In this paper, we described the evolution of the AGROVOC thesaurus to AGROVOC Concept Scheme based on OWL (web ontology language) model and now shifting to SKOS (simple knowledge organization system) model. The paper explained why and how it evolved highlighting the key differences between different models. The system architecture and significant set of features available in the VocBench was discussed in the paper.